Healing of the Acutely Injured Anterior Cruciate Ligament: Functional Treatment with the ACL-Jack, a Dynamic Posterior Drawer Brace - Matthias Jacobi; Nikolaus Reischl; Karolin Rönn; Robert A. Magnusson; Emanuel Gautier; Roland P. Jakob (Advances in Orthopedics)
Background. The injured anterior cruciate ligament (ACL) has a limited healing capacity leading to persisting instability. Hypothesis/Purpose. To study if the application of a brace, producing a dynamic posterior drawer force, after acute ACL injury reduces initial instability. Study Design. Cohort study. Methods. Patients treated with the ACL-Jack brace were compared to controls treated with primary ACL reconstruction und controls treated nonsurgically with functional rehabilitation. Measurements included anterior laxity (Rolimeter), clinical scores (Lysholm, Tegner, and IKDC), and MRI evaluation. Patients were followed up to 24 months. Results. Patients treated with the ACL-Jack brace showed a significant improvement of anterior knee laxity comparable to patients treated with ACL reconstruction, whereas laxity persisted after nonsurgical functional rehabilitation. The failure risk (secondary reconstruction necessary) of the ACL-Jack group was however 21% (18 of 86) within 24 months. Clinical scores were similar in all treatment groups. Conclusion. Treatment of acute ACL tears with the ACL-Jack brace leads to improved anterior knee laxity compared to nonsurgical treatment with functional rehabilitation.